KEUNGGULAN DAN KEKUATAN SISTEM EKONOMI PANCASILA - Mokhammad Fazar; Nizma Zaqlulsyah; Nur Islamiyah; Maulidyah Qurrotul A'yuni; Rully Maulidyah Andriana; Ani Faujiah (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
The advantages of the basic principles contained in the Pancasila economic system are equally related to the principles of humanity, economic nationalism, economic democracy which are embodied in a people's economy and justice. Of course, the concept of Pancasila economics itself is not just a practical theory in economic behavior, but is a discipline of economics with principles to allocate scarce and limited resources to be used rationally so as to achieve maximum results for the welfare of all Indonesian people. Pancasila economy is a joint effort based on the principle of national cooperation, which can also aim to realize social justice in shared prosperity and prosperity. Keywords: Superiority, Pancasila Economic System References Muhammad Hatta, Politik Kebangsaan dan Ekonomi, [Jakarta: PT. Kompas Media Nusantara, 2015], 393. Kaelan, Pendidikan Pancasila, [Yogyakarta: Paradigma, 2014], 4 - 5. Sukarno, Filsafat Pancasila Menurut Bung Karno, Jakarta, Media Prassendo, 2016. Sulastomo,” Cita-cita Negara Pancasila “, Jakarta, PT. KOMPAS Media Nusantara, 2014. Sri-Edi Swasono, Sistem Ekonomi dan Demokrasi Ekonomi, (Jakarta: UI Press, 1987), Cet. Ke-2, 122 Mubyarto, Pemberdayaan Ekonomi Rakyat dan Peranan Ilmu-ilmu Sosial (Yogyakarta: Gadjah Mada University Press, 2002), 28. Swasono Sri-Edi, Sistem Ekonomi dan Demokrasi Ekonomi, Jakarta: UI Press, 1987. Wahid Abdurrahman,” Islamku, Islam Anda, Islam Kita “, Jakarta, Projeck Demokrasi, 2011. http://www.ekonomikerakyatan.ugm.ac.id./my%20Web/sembul//59.htm Abdurrahman Wahid, Islamku, Islam Anda, Islam Kita, (Jakarta: Projeck Demokrasi, 2011), 183. https://ojs.unpkediri.ac.id/index.php/pinus Abdul Madjid dan Sri-Edi Swasono, Wawasan Ekonomi Pancasila, (Jakarta: UI Press, 1998), 32-33. https://www.maxmanroe.com/vid/bisnis/sistem-ekonomi-pancasila.html V.Wiratna Sujarweni,Metodeologi Penelitian ( Yogyakarta : Pustaka Baru Perss, 2014), h.57..